Quantitative Characterization of Full-Spectrum Pore Size and Connectivity for Shale with Different Sedimentary Facies from the Dongying Depression, Bohai Bay Basin, East China. (31st May 2022) - Du, Yushan; Yin, Na; Hu, Qinhong; Meng, Mianmo; Zhu, Xiuchuan; Chao, Jing; Ma, Cunfei
Abstract : Working with shales in the fourth member of Shahejie Formation in the Dongying Depression in Bohai Bay Basin of East China, this study examines the facies classification, petrological characteristics, pore size distribution, and pore connectivity of oil-producing shale. The studied shales could be classified into five sedimentary facies according to a three-step classification criterion that consists of total organic carbon (TOC), sedimentary structure, and mineral composition. Among them, the "low TOC massive siliceous mudstone" and "low TOC layered clayey mudstone" facies have similar distributions from low-pressure N2 physisorption, and the incremental volume within the 3-30 nm pore size range is much higher than the "high TOC laminated clayey marlstone" and "low TOC layered siliceous marlstone" facies. The T 2 spectra of nuclear magnetic resonance tests for the "high TOC laminated clayey marlstone" facies which contains abundant calcite laminae and organic matter-hosted pores commonly show three peaks, with a dominant peak at less than 300 nm in diameter and good pore connectivity. The T 2 spectra of three other facies are both characterized by two peaks, and the main peak of the "low TOC layered siliceous marlstone" and "low TOC layered clayey mudstone" facies has a similar range at 2-500 nm, in contrast with 1-17 nm for the "low TOC massive siliceous mudstone" facies. Pores in these four facies are mainly at nanoscales with predominant pore-throat diameters at less than 50 nm; however, the "high TOC laminated clayey marlstone" facies has the largest peak in the range of >1 μ m, possibly because of its interlaminar structure and microcracks. The spontaneous imbibition experiments using two distinct fluids indicated that all of four facies have a much better pore connectivity towards the hydrophilic fluid than these experienced by the hydrophobic fluid.